2017
DOI: 10.3892/ol.2017.5837
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine-like factor-like MARVEL transmembrane domain-containing 3 expression is associated with a favorable prognosis in esophageal squamous cell carcinoma

Abstract: Abstract. Decreased expression of human chemokine-like factor-like MARVEL transmembrane domain-containing 3 (CMTM3) has been identified in a number of human tumors and tumor cell lines, including gastric and testicular cancer, and PC3, CAL27 and Tca-83 cell lines. However, the association between CMTM3 expression and the clinicopathological features and prognosis of esophageal squamous cell carcinoma (ESCC) patients remains unclear. The aim of the present study was to investigate the correlation between CMTM3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Esophageal carcinoma is one of the most common malignant tumors in China, which accounts for the sixth most common cause of cancer-related death in the world. 1 , 2 Surgical resection is the main treatment for esophageal cancer patients; however, the 5-year survival rate of esophageal cancer patients after surgery is still less than 25%. 3 , 4 Currently, the incidence of esophageal carcinoma is still increasing in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal carcinoma is one of the most common malignant tumors in China, which accounts for the sixth most common cause of cancer-related death in the world. 1 , 2 Surgical resection is the main treatment for esophageal cancer patients; however, the 5-year survival rate of esophageal cancer patients after surgery is still less than 25%. 3 , 4 Currently, the incidence of esophageal carcinoma is still increasing in China.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Currently, the incidence of esophageal carcinoma is still increasing in China. 1 , 5 , 6 The early diagnosis of esophageal carcinoma is a tough challenge. 7 , 8 Thus, it would be meaningful to explore novel molecular biomarkers associated with the early diagnosis and prognosis of esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the CMTM3 promoter differs from those of other CMTM family members due to its typical CpG island. CMTM3 is known to be involved in tumor suppression; however, the methylation of the CMTM3 promoter has been shown to suppress CMTM3 expression in various cancer types, such as gastric, male laryngeal, esophageal, breast, nasopharyngeal, and colon carcinomas (8,(34)(35)(36). In the study of Li et al, CMTM3 was demonstrated to trigger G2 cell-cycle arrest and apoptosis in a p53-independent manner, leading to inhibition of the proliferative and migratory abilities of testicular cancer cells (NCCIT) (37).…”
Section: Discussionmentioning
confidence: 99%
“…International Publisher has different biological functions in different tumors, although they collectively play a suppressive role. Many cancers of the digestive tract such as esophageal, gastric, and oral cancer involve CMTM3 in several different pathways [28][29][30][31][32][33], while, cancers of digestive glands, like hepatocellular carcinoma, are also associated with CMTM members [34,35]. Moreover, researches in genitourinary cancers indicate that CMTM3 and CMTM8 suppress tumor cell reproduction and migration [36][37][38][39][40].…”
Section: Ivyspringmentioning
confidence: 99%